"Hand-to-mouth" citizenship: decision time for the UK Supreme Court on the substance of Zambrano rights, EU citizenship and equal treatment. Issue 2 (2nd April 2016) - O'Brien, Charlotte
Abstract: UK benefit rules strip Zambrano residence rights, for UK national children and their third country national primary carers, of equal treatment entitlement. These rules are challenged in a case pending before the UK Supreme Court. This piece argues that Zambrano creates an EU-citizenship-based right to reside which necessarily entails equal treatment. UK national children in Zambrano families fall within the scope of EU law so are not prevented by the wholly internal rule from claiming equal treatment with EU national children in Teixeira families. And they are protected by equal treatment as a general principle of EU law, which requires equal treatment with other UK national children. The justifications for automatic unequal treatment put forward before, and accepted with alacrity by, the Court of Appeal, are poorly reasoned and ill-matched with the rules in question – most notably because Zambrano families may have strong connections with the UK. A CJEU reference is likely; a Zambrano right is the right to reside in the Union – it is the right to have EU rights. The substance of EU citizenship is at stake.